Trading in turbulent times: Smallholder maize marketing in the southern highlands, Tanzania - Van Campenhout, Bjorn; Lecoutere, Els; D'Exelle, Ben (International Food Policy Research Institute, 2011)
The short-run effects of the 2007/2008 global food crisis on semisubsistence farmers' well-being in low-income countries depends on whether they are net sellers or net buyers of the affected commodities. Realizing that farmers face volatile prices over the course of an agricultural year, we analyze the timing of sales and purchases of maize. In addition, in our analysis, we depart from the oft-made assumption that farmers in rural villages are perfectly integrated within the wider economy. Comparing our results with a static analysis, we find that especially-poor farmers face greater losses from the maize food price crisis than others. The welfare impact is likely to be even more severe than previously thought, as the crisis hurts large households with relatively large numbers of children and women most. We also analyze the effects of factors that are likely to affect potential benefits from intertemporal and spatial price dispersion, such as means of transport, access to price information, and credit.